2012
DOI: 10.3892/or.2012.2100
|View full text |Cite
|
Sign up to set email alerts
|

4-Methylumbelliferone leads to growth arrest and apoptosis in canine mammary tumor cells

Abstract: Abstract. Hyaluronan (HA), a major component of the extracellular matrix (ECM), is synthesized by HA synthase (HAS) 1, HAS2 and HAS3 and is intricately involved in cell growth and metastasis. The HA synthesis inhibitor 4-methylumbelliferone (4-MU) has been reported to exhibit anticancer properties in various types of malignant tumors. However, the underlying mechanisms at the molecular and cellular levels remain unclear. In this study, to establish an animal model for studying the function of HA in human breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 42 publications
1
23
0
1
Order By: Relevance
“…Furthermore, it has been demonstrated that 1.0 mM MU exerts its anti-tumor effect on ovarian cancer by suppressing thymidine phosphorylase expression (11). In another study, Saito et al (12) indicated that MU leads to growth arrest and apoptosis mediated by BAX expression and a reduction in HA synthesis. In the present study, the induction of apoptosis by MU in HT1080 cells was observed, suggesting that the intracellular signaling pathway of apoptosis affected by 100 µM MU and is not dependent on the type of tumor.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, it has been demonstrated that 1.0 mM MU exerts its anti-tumor effect on ovarian cancer by suppressing thymidine phosphorylase expression (11). In another study, Saito et al (12) indicated that MU leads to growth arrest and apoptosis mediated by BAX expression and a reduction in HA synthesis. In the present study, the induction of apoptosis by MU in HT1080 cells was observed, suggesting that the intracellular signaling pathway of apoptosis affected by 100 µM MU and is not dependent on the type of tumor.…”
Section: Discussionmentioning
confidence: 97%
“…4-methyl umbelliferone (4-MU) has been reported to lead to HA synthesis by depleting the cellular UDP-glucoronic acid and downregulating HAS2 and HAS3 [5]. HepG2 and the higher HA containing HepR21 cells, were grown and exposed to different concentrations of 4-MU (0.25, 0.50, 1 and 2 mM) for either 6 or 12 hours as per the experiment along with a set of untreated cells acting as control.…”
Section: Methodsmentioning
confidence: 99%
“…Altered HA synthesis in tumor cells by HAS activity accelerates tumor growth through the recruitment of HA rich stromal cells and vasculature aided by factors secreted by tumor cells themselves [3], [4]. Consequently, HA synthase inhibitor, 4-MU has been reported to act as anti-tumor agent leading to decreased HA level, growth arrest and apoptosis [5], [6]. Although high molecular weight HA has been observed to enhance cellular proliferation, HA oligosaccharides inhibit anchorage independent growth in tumor cells by suppressing the PI3 Kinase/Akt survival pathway by stimulating expression of the tumor suppressor PTEN [7].…”
Section: Introductionmentioning
confidence: 99%
“…4-Methylumbelliferone (4-MU) or 7-hydroxy-4-methylcoumarin is a well-studied inhibitor of HA synthesis (Clarkin, Allen, Wheeler-Jones, Bastow, & Pitsillides, 2011; Kakizaki et al, 2004, 2002; Morohashi et al, 2006; Nakamura et al, 1997; Saito et al, 2013). Mammalian cells synthesize HA, using two building blocks—UDP-glucuronic acid (UGA) and UDP- N -acetyl-D-glucosamine.…”
Section: Targeting Ha Productionmentioning
confidence: 99%
“…In several studies using tumor cell lines, the IC 50 of 4-MU for inhibiting HA synthesis is in the range of 400 μM (Kakizaki et al, 2004, 2002; Lokeshwar et al, 2010; Nakamura et al, 1997). Recently, it has also been shown that 4-MU downregulates HAS2 and HAS3 expression (Saito et al, 2013). The study showed that 4-MU indeed inhibits both HA and sulfated glycosaminoglycan synthesis in the chick limb bud micromass culture (Clarkin et al, 2011).…”
Section: Targeting Ha Productionmentioning
confidence: 99%